Significant association between clinical characteristics and changes in peripheral immuno-phenotype in large vessel vasculitis - Matsumoto, Kotaro (Arthritis Res Ther, 2019)
BACKGROUND: Large vessel vasculitis (LVV) is a type of vasculitis characterized by granulomatous inflammation of medium- and large-sized arteries. Clinical assessment of acute phase reactants has been conventionally used to diagnose and monitor diseases; however, accurate assessment of vascular disease activity status can be difficult. In this study, we investigated comprehensive immuno-phenotyping to explore useful biomarkers associated with clinical characteristics. METHODS: Consecutive patients with newly diagnosed LVV who visited our institution between May 2016 and May 2019 were enrolled. The number of circulating T cells, B cells, natural killer cells, dendritic cells, monocytes, and granulocytes was examined and chronologically followed. Baseline and time-course changes in immuno-phenotyping associated with disease activity were assessed. RESULTS: Comprehensive immuno-phenotyping data from 90 samples from each of 20 patients with LVV were compared with those from healthy controls (HCs). The number of helper T (Th), follicular helper T (Tfh), CD8(+) T, CD14(++) CD16(+) monocytes, and neutrophils were higher in patients with giant cell arteritis (GCA) and/or Takayasu arteritis (TAK) than in HCs. Among them, the number of CD8(+) T and CD8(+) Tem were higher in patients with TAK than in GCA. Notably, memory CD4(+) and CD8(+) T cells in patients with TAK remained high even in the remission phase. Further analysis revealed that the number of Th1, Th17, and Tfh cells was associated with disease relapse in GCA and TAK and that the number of CD8(+) T cells was associated with relapse in TAK. Th1, Th17, and Tfh cells decreased after treatment with biologic agents, while CD8(+) T cells did not. CONCLUSIONS: Our results from peripheral immuno-phenotyping analysis indicate that the numbers of Th and Tfh cells changed along with the disease condition in both GCA and TAK, while that of CD8(+) T cells did not, especially in TAK. Treatment with biologic agents decreased the proportion of Th and Tfh cells, but not CD8(+) T cells, in the patients. Chronological immuno-phenotyping data explained the difference in therapeutic response, such as reactivities against biologics, between GCA and TAK.